DEVELOPMENT OF SOCIAL VALUES AMONG MADRASA STUDENTS - Dulkiah, Moh.; Wildan, Asep Dadan (Ikatan Dosen Menulis, 2022)
This This study aims to determine the development of social values ​​in madrasah students. This research was conducted in the area of ​​West Java, Banten and DKI Jakarta. The research was conducted on madrasah students with the proportion at primary, Yunior High School and Senior High School. This study found that character development among madrasah students has effectiveness by developing models of developing character education in the form of teaching, habituation, imitation, motivation and enforcement of rules. Social values ​​are taught in every activity, both in the madrasa and in the Islamic boarding school for those under the Islamic boarding school. Values ​​education is oriented towards improving the character and attitudes of students in social life. The instilled social values ​​also vary, including religious values, independence values, and responsibility values. The application of value education has effectiveness in strategy, program, process, and evaluation and has an integral form where one element with the other has a multiplayer effect. The elements that exist are theoretically inseparable so that the success of a character education in Islamic boarding schools is shown by the synergy of these elements.